Different Cognitive Profiles of Patients with Severe Aphasia - Chiara Valeria Marinelli; Simona Spaccavento; Angela Craca; Paola Marangolo; Paola Angelelli (Behavioural Neurology)
Cognitive dysfunction frequently occurs in aphasic patients and primarily compromises linguistic skills. However, patients suffering from severe aphasia show heterogeneous performance in basic cognition. Our aim was to characterize the cognitive profiles of patients with severe aphasia and to determine whether they also differ as to residual linguistic abilities. We examined 189 patients with severe aphasia with standard language tests and with the CoBaGA (Cognitive Test Battery for Global Aphasia), a battery of nonverbal tests that assesses a wide range of cognitive domains such as attention, executive functions, intelligence, memory, visual-auditory recognition, and visual-spatial abilities. Twenty patients were also followed longitudinally in order to assess their improvement in cognitive skills after speech therapy. Three different subgroups of patients with different types and severity of cognitive impairment were evidenced. Subgroups differed as to residual linguistic skills, in particular comprehension and reading-writing abilities. Attention, reasoning, and executive functions improved after language rehabilitation. This study highlights the importance of an extensive evaluation of cognitive functions in patients with severe aphasia.